1993
DOI: 10.3109/10731199309117651
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Attachment and Growth of Human Endothelial Cells Derived from Umbilical Veins on Ammonia Plasma Modified Surfaces of Ptfe and EPTFE Synthetic Vascular Graft Biomaterials

Abstract: Ammonia plasma generated by electrical discharge at low pressure was employed for the surface modification of PTFE and ePTFE. A new chemistry at the plasma treated surfaces is reported. X-ray photoelectron spectroscopy studies showed the incorporation of C-N, C-O, C = O etc functional groups on the plasma treated surfaces. Human endothelial cells derived from umbilical veins (HUEC) were used to seed the plasma treated PTFE and ePTFE surfaces to assess the attachment and growth. Enhanced attachment and growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…5, virgin PTFE does not promote the ECs adhesion due to the very low surface energy of this polymer. Conversely, the ammonia plasma-treated PTFE is by far the most efficient surface for supporting cell adhesion, in good agreement with data previously published by the Sipehia's group [29][30][31]. Despite this behavior, it has been shown in many instances that the adhesion of ECs on ammonia plasma-treated PTFE is a non-specific phenomenon, therefore is non-viable in real in vivo situations.…”
Section: Vegf Loading and Immunodetectionsupporting
confidence: 82%
“…5, virgin PTFE does not promote the ECs adhesion due to the very low surface energy of this polymer. Conversely, the ammonia plasma-treated PTFE is by far the most efficient surface for supporting cell adhesion, in good agreement with data previously published by the Sipehia's group [29][30][31]. Despite this behavior, it has been shown in many instances that the adhesion of ECs on ammonia plasma-treated PTFE is a non-specific phenomenon, therefore is non-viable in real in vivo situations.…”
Section: Vegf Loading and Immunodetectionsupporting
confidence: 82%
“…This suggestion seems to be supported by the results of recent studies where it was shown that the treatment of polymeric membranes with ammonia plasma promoted adsorption and immobilization of fibronectin and vitronectin, and enhanced the attachment and proliferation of human endothelial cells. 41,45,47 The treatment of the polylactide membranes used in the present study with sulphur-containing plasma had a negative effect on cell parameters. This may be due to the fact that incorporation of the OSH groups into the polylactide membranes makes them resistant to the nonspecific adsorption of proteins, which in turn, diminishes the attachment and proliferation of cells in culture.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore sought to compare the effect of plasma treatments on the surface modification of PET fibres and PET films, with emphasis on ammonia plasma treatments that promote the formation of surface amino groups which are recognised as improving cell adhesion and, [24][25][26] more importantly, may potentially also be used for further biomolecule conjugation [27,28]. To this end, we examined the dependence between PET structure geometry and plasma treatment duration.…”
Section: Introductionmentioning
confidence: 99%